An unexpected culprit: Intraosseous vascular malformation in the elderly man’s tibia revealed by magnetic resonance imaging (Indian Journal of Case Reports, 2025)
Intraosseous vascular malformations (IVMs) are rare, benign vascular anomalies within bone that may cause diagnostic confusion due to their infrequent presentation and subtle radiologic features. They can mimic neoplastic or inflammatory bone conditions, and their clinical presentation is often vague. Magnetic resonance imaging (MRI) plays a vital role in delineating these anomalies. This paper presents a case of suspected IVM of the right tibia, identified on MRI, with associated findings of superficial venous dilation. We herein report the case of a 67-year-old male who presented with complaints of swelling and pain in the right lower leg with slight restriction of movement. On radiograph, there was a mixed osteolytic and sclerotic lesion in the middle third of the right tibia mimicking a fibrous tumor. However, MRI revealed a dilated nutrient artery that was forming clusters at the distal tibia, providing the clue for the diagnosis of arteriovenous malformation.